CLINICAL AND BIOCHEMICAL INDICATORS OF HEMOLYTIC DISEASE OF NEWBORNS - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Abduzhalolova Firuza Abduazizovna (TADQIQOTLAR.UZ, 2024)
Annotation.    The  article  discusses  current  problems  of  obstetrics  and neonatology,  in  particular  hemolytic  disease  of  newborns.  Hemolytic  disease  of newborns is a common cause of miscarriage, complications during childbirth and the perinatal period. The level of bilirubin, hemoglobin and reticulocytes in the blood of newborns was determined.